2008
DOI: 10.1021/es703143g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of Oxidation of Antibacterial Agents by Manganese Oxide

Abstract: Several groups of popular antibacterial agents (i.e., phenols, fluoroquinolones, aromatic N-oxides, and tetracyclines) were demonstrated in earlier studies to be highly susceptible to oxidation by manganese oxides, a common oxidant in soils. However, because of the high complexity, the reaction kinetics were not fully characterized. A mechanism-based kinetic model has now been developed to successfully describe the entire range of kinetic data for a total of 21 compounds of varying structural characteristics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
144
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(158 citation statements)
references
References 27 publications
13
144
1
Order By: Relevance
“…It is also possible that the heterogeneous degradation in the presence of MnO2 involves the formation of precursor complex between the dye and surface bound Mn. 46 Electrons from the activated dye move to the Mn(IV) on the surface of MnO2. Consequently, the dye undergoes oxidative degradation.…”
Section: Figure 7 Effect Of Ph On the Photocatalytic Degradation Of mentioning
confidence: 99%
“…It is also possible that the heterogeneous degradation in the presence of MnO2 involves the formation of precursor complex between the dye and surface bound Mn. 46 Electrons from the activated dye move to the Mn(IV) on the surface of MnO2. Consequently, the dye undergoes oxidative degradation.…”
Section: Figure 7 Effect Of Ph On the Photocatalytic Degradation Of mentioning
confidence: 99%
“…5(b)). The electrochemical oxidation of tetracycline would lead to the production of intermediates, which may also simultaneously be degraded on the anode by direct electron transfer and by hydroxyl radicals according to the reaction [2] . The decrease in rate of tetracycline degradation may be due to the competitive reaction of the daughter compounds with the parent compound on the anode.…”
Section: Asia-pacific Journal Of Chemical Engineeringmentioning
confidence: 99%
“…[1] Among various pharmaceutical compounds, antibiotics are of special concern because of their extensive use in human and veterinary medicine and their potential to promote growth of resistant bacteria and pose adverse health effects to humans. [1,2] As a result of their antibacterial nature, antibiotic residues cannot be effectively destructed by traditional biological methods. [3] Although antibiotics could be removed by physical processes such as granular activated carbon filtration, [4] they were just transferred to another medium (carbon), which requires further treatment and disposal.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation reaction begins with the formation of a precursor complex between the pollutant and the surface-bound metallic species, followed by electron transfer within the complex and release of an organic cationic radical, that will evolve to an oxidized form or bind to a vicinal reactive species. Through the development of a mechanism-based kinetic model, Zhang et al (2008) demonstrated that environmental factors may affect either the reaction kinetics of MnO 2 -pollutant complex formation or the rate of electron transfer, directly or through action on the reactive surface sites. Among solutes, Mn(II) presents the strongest inhibitory effect, followed by other divalent cations as Ca 2+ .…”
Section: Oxidation and Reductionmentioning
confidence: 99%